2010
DOI: 10.1002/ptr.2899
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of oral administration of nutrient mixture, quercetin and red onions on the bioavailability of epigallocatechin gallate from green tea extract

Abstract: Epigallocatechin gallate (EGCG), a main anticancer component in green tea, has a poor bioavailability in rats and humans due to oxidation, metabolism and its efflux. It was hypothesized that nutrients that address these problems might result in increased bioavailability. Plasma concentrations of EGCG at various time intervals were determined to calculate and compare the pharmacokinetic parameters after oral administration of green tea extract (GTE) or GTE as a nutrient mixture (E) or E + quercetin (Q)/red onio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…However, because of instability, the bioavailability of catechins in vivo remained low. [15][16][17] Thus, through preparation of microemulsion or nanoemulsion for encapsulation of bioactive compounds such as catechin, it is possible to enhance stability so that both bioavailability and biological activity of catechins can be greatly enhanced. More importantly, the efficiency dose of catechins can be reduced substantially to minimize side effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of instability, the bioavailability of catechins in vivo remained low. [15][16][17] Thus, through preparation of microemulsion or nanoemulsion for encapsulation of bioactive compounds such as catechin, it is possible to enhance stability so that both bioavailability and biological activity of catechins can be greatly enhanced. More importantly, the efficiency dose of catechins can be reduced substantially to minimize side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, EGCG has become one of the most popular phytochemicals in the study of cancer treatment. However, poor bio-availability, susceptibility to oxidation, first-pass metabolism and rapid efflux has been the major hurdles in drug development [18][19][20]. Investigators have shown that the absolute bio-availability of EGCG, EGC and EC after intra-gastric administration of decaffeinated green tea is 0.1%, 14% and 31% [21].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The effectiveness of curcumin, however, can be potentiated simply by using a combination of the compound and other polyphenols. This constitutes one of the most natural ways to improve the efficiency of curcumin action, and effectively increase its bioavailability [24,25] .…”
Section: Cell Staining and Analysis For γH2ax And The Cell Cyclementioning
confidence: 99%